Implications of Good Corporate Governance (GCG) on Financial Statement Integrity - Kezia Julia Putri (International Journal of Asian Business and Management, 2023)
The development of a strategy by the government as a public organization to deal with the implementation of good corporate governance, which is now a requirement for each company in order to win global business competition and also overtake the problem of the economic crisis, is required by the rapid and massive advances in information technology that have occurred during the industrial revolution 4.0 era. The Agency theory was utilized to support this research since it fosters the formation of the notion of Good Corporate Governance in managing the company's business to reduce agency conflicts. Companies are required to be able to provide good financial reports. A solid financial report is one that maintains the integrity of the information it contains. The extent to which financial reports reflect financial facts fairly, honestly, and not more or less is referred to as their integrity. The goal of this study is to identify the implicit influence of good corporate governance (GCG) on the financial statements of different Indonesian enterprises. Research data is collected through financial reports and company annual reports. The SPSS statistical software was used to analyze the research data. The study's findings indicate that institutional share ownership and  management support as part of Good Corporate Governance have a significant impact on the financial statements of Indonesian enterprises